Journal Review: Effectiveness of Supplementary Feed Ingredients on Egg Productivity and Body Weight Gain of Balibangtan Superior Hens - Laraswati, Maria Intan Ayu; Nugraha, Raden Septiarani Jati; Hidayah, Nurulia; Ridlo, Muhammad Rosyid (Universitas Airlangga, 2025)
Feed is a major determining factor in the success of layer and broiler farming. The nutritional content of the feed must meet the requirements to increase livestock productivity. To improve chicken performance, we use additional feed. This review aims to determine the effectiveness of feed ingredients as a feed supplementation for chickens by using production waste, forage, household waste, forage, and enzymes to increase the growth and production of KUB chickens. Ingredients that can be used as feed additives include coconut pulp, pumpkin waste flour, papaya leaf waste, teak leaf extract, moringa leaves, tilapia plants, betel leaf juice, BS4, selenium chitosan, phytase, xylooligosaccharide, kesum leaf flour, sago pulp, spinach waste, and BSF maggot. The results of this review showed that the most effective feed ingredient was the supplementation of teak leaf extract (Tectona grandis), with a protein content of 4.9%, being the most effective feed ingredient in increasing egg productivity up to 15%. The supplementation of kesum leaf flour, with an average body weight gain of 426.97 g/head, is the most effective feed ingredient for increasing body weight growth in KUB chickens.